Average Intensity and Beam Quality of Hermite-Gaussian Correlated Schell-Model Beams Propagating in Turbulent Biological Tissue - Zhang, Hanghang; Cui, Zhiwei; Han, Yiping; Guo, Jirong; Chang, Chao (Frontiers in Physics, 2021)
The propagation characteristics of a Hermite-Gaussian correlated Schell-model (HGCSM) beam in the turbulence of biological tissue are analyzed. The average intensity, spectral degree of coherence, and the dependence of the propagation factors on the beam orders, transverse coherence width, fractal dimension, characteristic length of heterogeneity, and small length-scale factor are numerically investigated. It is shown that the HGCSM beam does not exhibit self-splitting properties on propagation in tissues due to the strong turbulence in the refractive index of biological tissue. The larger the beam orders, the fractal dimension, and the small length-scale factor are, or the smaller the transverse coherence width and the characteristic length of heterogeneity are, the smaller the normalized propagation factor is, and the better the beam quality of HGCSM beams in turbulence of biological tissue is. Moreover, under the same condition, the HGCSM beam is less affected by turbulence than of Gaussian Schell-model (GSM) beam. It is expected that the results obtained in this paper may be useful for the application of partially coherent beams in tissue imaging and biomedical diagnosis.